Nutrient release capability in Nordic and Baltic forest soils determined by dilute nitric acid extraction – Relationships with indicators for soil quality, pH and sustainable forest management. (January 2019) - Callesen, Ingeborg; Clarke, Nicholas; Lazdinš, Andis; Varnagiryte-Kabasinskiene, Iveta; Raulund-Rasmussen, Karsten
Highlights: Phosphorus (P) pool in 23 forest soils was 0–4 Mg ha −1 by dilute HNO3 extraction. Soil texture and pH were ambiguous predictors for nutrient release. In Al-Fe oxide buffered soils base cation loss is not reflected by a clear pH decline. Soil test methods can predict the ability to recover from P and base cation depletion. Mapping of soils can aid the monitoring of sustainable biomass harvest and regrowth. Abstract: The long-term carrying capacity for biomass production is highly dependent on available soil resources. A soil test method for potential nutrient release capability was applied to 23 Nordic and Baltic forest soil profiles. The soils had coarse (10), medium (12) and fine (1) soil texture and most were podsolising. Extraction with dilute (0.1 M, 1:50 sample:solution ratio) nitric acid for 2 h was followed by 48 h and 168 h of extraction in soil samples from pedogenetic horizons. Dilute nitric acid solution was replaced after each step and release of mineral nutrient elements in solution was determined. C-horizon nutrient release (µmol g −1 fine earth, 0–218 h) was negatively correlated with mean annual temperature (MAT 0.5–8.5 °C) and for potassium (K) also mean annual precipitation (MAP 523–1440 mm y −1 ) suggesting a gradient in the mineralogy of the parent material that sediment transports during Pleistocene glaciations have not distorted. In B-horizons of sandy parent materials with felsic mineralogy cumulative nutrient release was positively correlated with pH and with Al and Fe release suggesting accumulation and stabilisation of nutrients in pedogenic products. E-horizons had less nutrient release capability than C-horizons, indicating a more weathered state of E-horizon parent material. Soil formation due to mineral dissolution and leaching of base cations and the gradient in parent material origin and weathering state both affected the observed pattern of nutrient release. On soils with very low mineral P resources (e.g. <250 kg P ha −1 to 50 cm) by repeated dilute acid extraction, harvest of nutrient rich biomass will not be sustainable. However, it can't be concluded that sites with high P availability by 0.1 M HNO3 can support an intensive harvest without compensation of P (and Ca) by fertilisation. Due to buffering of removed base cations in B-horizons, nutrient export with biomass may not be traceable as pH decline at decadal time scale. Therefore, the direct measurement of nutrient stocks by the extraction procedure (or other similar assessment of nutrient reserves by strong acid) is suggested as indicative for the mineral weathering capability of forest soils to recover from P and base cation depletion by biomass harvest.